2013
DOI: 10.1021/bi400228e
|View full text |Cite
|
Sign up to set email alerts
|

Role of Arg228 in the Phosphorylation of Galactokinase: The Mechanism of GHMP Kinases by Quantum Mechanics/Molecular Mechanics Studies

Abstract: GHMP kinases are a group of structurally related small molecule kinases. They have been found in all kingdoms of life and are mostly responsible for catalyzing the ATP-dependent phosphorylation of intermediary metabolites. Although the GHMP kinases are of clinical, pharmaceutical, and biotechnological importance, the mechanism of GHMP kinases is controversial. A catalytic base mechanism was suggested for mevalonate kinase that has a structural feature of the γ-phosphate of ATP close to an aspartate residue; ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
44
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 22 publications
(49 citation statements)
references
References 54 publications
5
44
0
Order By: Relevance
“…10 Two conserved catalytic residues (Ser141 and Ser142) in galactokinase stabilize ATP in the oxyanion hole. Although the coordination environment of the Mg 2+ ion in the two GHMP kinases is different, we identified the corresponding functional residues in PMK by careful comparison of structures of galactokinase and PMK obtained from MD simulations.…”
Section: Qm/mm Calculationsmentioning
confidence: 99%
See 2 more Smart Citations
“…10 Two conserved catalytic residues (Ser141 and Ser142) in galactokinase stabilize ATP in the oxyanion hole. Although the coordination environment of the Mg 2+ ion in the two GHMP kinases is different, we identified the corresponding functional residues in PMK by careful comparison of structures of galactokinase and PMK obtained from MD simulations.…”
Section: Qm/mm Calculationsmentioning
confidence: 99%
“…45 GTMP kinases are different from classical kinases in that such a lysine is absent in the motif II p-loop, 10 except for PMK, which contains a lysine at the end of the p-loop. However, we have previously found that a positively charged residue (Arg228) in galactokinase can reorientate toward ATP to facilitate the phosphoryl transfer.…”
Section: Effect Of Sequence Alterations On Mg 2+ Coordinationmentioning
confidence: 99%
See 1 more Smart Citation
“…65,91,92,101 Here it will be presented theoretical studies in PKA, CDK2 and galactokinase (GALK) related with the finding of this mechanism. Some studies in the kinase PKA supported this mechanism in contrast to those mentioned above.…”
Section: Substrate-assisted Mechanismmentioning
confidence: 99%
“…It should be remarked that Smith et al related this conclusion to the exclusion of the Asp from the QM region in the QM/MM simulations. Huang et al 101 located the substrate-assisted mechanism in GALK where the phosphoryl group is transferred from the ATP to the oxygen of one OH group of the substrate galactose. QM/MM simulations within a two-layer ONIOM method were carried out.…”
Section: Substrate-assisted Mechanismmentioning
confidence: 99%